2014
DOI: 10.4314/tjpr.v13i10.11
|View full text |Cite
|
Sign up to set email alerts
|

Antidiarrhea and antioxidant activities of Honokiol extract from <i>Magnoliae officinalis cortex</i> in mice

Abstract: Purpose: To evaluate the antidiarrhea and antioxidant properties of honokiol extracted from Magnoliae officinalis cortex (bark of Magnolia officinalis), an important medical material in traditional Chinese 16 % in comparison with -neostigmine control group-(59.0 % vs. 70 .1%). Compared with control (no honokiol), the activities of catalase (CAT), glutathione peroxidase (GSH-Px) and total superoxide dismutase (T-SOD) in the plasma (CAT, 7.31 vs. 13.21 U/mL; 439.6 vs. 608.9 U/m; 82.2 vs. 109.8 U/mL) and liver (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
(27 reference statements)
0
15
0
2
Order By: Relevance
“…These pharmacological activities could be mediated by the phytochemical constituents of Bryophyllum pinnatum [ 25 ]. The presence of phytoconstituents like alkaloids, terpenes, glycosides, and flavonoids has been reported on B. pinnatum and the antidiarrheal and antioxidant activities of these phytoconstituents have been reported as well [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pharmacological activities could be mediated by the phytochemical constituents of Bryophyllum pinnatum [ 25 ]. The presence of phytoconstituents like alkaloids, terpenes, glycosides, and flavonoids has been reported on B. pinnatum and the antidiarrheal and antioxidant activities of these phytoconstituents have been reported as well [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in intestinal transit may be due to reduced peristalsis which can be attributed to relaxation of the intestinal smooth muscle [ 30 , 31 ]. Drugs that relax the intestinal smooth muscles are often used as antidiarrheal agent because they inhibit intestinal hypermotility (increase peristalsis) which usually accompanies diarrhea [ 26 ]. Antidiarrheal activity of loperamide is linked to inhibition of peristalsis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the application of diarrhea index in the diarrhea model to reflect the degree of loose stools not only can consider the changes in the amount of loose stools, but also can consider the quality of loose stool, which is more comprehensive and objective than the single use of loose tool rate and loose tool level and can produce more comparable results [ 13 , 14 ]. The diarrhea index was normal in mice, and statistical treatment could be carried out according to the parameters [ 15 ]. Thus, in the present study, diarrhea index was used for evaluation of the degree of diarrhea in mice.…”
Section: Discussionmentioning
confidence: 99%
“…ALSG is the ratio of the sum of LSG of each loose stool to the total number of loose stools within an animal. DI is the result of LSR multiplying ALSG [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Asian herbal medicine, Magnolia flowers and bark have been used to treat symptoms such as headache, thrombotic stroke, gastrointestinal disorders, anxiety, and allergies [ 3 , 4 ]. The use as a medicinal product is based on a substantial number of different phytochemicals with anxiolytic [ 4 ], antiplatelet [ 5 ], antipyretic [ 6 ], anti-inflammatory [ 6 ], antidiarrheal [ 7 ], antioxidant [ 7 ], anti-stomach ulcer [ 8 ], and anti-allergic properties [ 9 ]. Magnolia denudata Desr.…”
Section: Introductionmentioning
confidence: 99%